Analisis Kesulitan Menyelesaikan Soal Dimensi Tiga Ditinjau Dari Tingkat Pemahaman Siswa Kelas XII MAN 2 Pesisir Selatan - Benita Widya Astuti; khairudin khairudin; Susi Herawati; Fazri Zuzano; Niniwati Niniwati (Jurnal Tunas Pendidikan, 2022)
This research is a qualitative descriptive study with the aim of knowing the form of difficulty and the factors that cause students' difficulties in solving 3D questions in terms of the level of understanding of class XII students of MAN 2 Pesisir Selatan. The subjects in this study were 31 students of class XII IPA. The data in this study were obtained from written tests and interviews. The results showed that students with a high level of understanding had no difficulty in solving problems. All indicators of understanding have been achieved and are called low level difficulty type. Students with a moderate level of understanding have difficulty on the third and fifth indicators, including the type of moderate level of difficulty. The results of the interview showed that students had difficulty in solving problems because they were not careful in the steps of the process, it was difficult to relate various concepts and imagine. Students with low levels of understanding have difficulty on all indicators except for the second indicator and this is included in the type of high level of difficulty.